Limited Wegener's Granulomatosis Presenting with an Isolated Abduction Deficit. (June 2014) - Chen, John J.; Hong, Sandy; Kirby, Patricia A.; Policeni, Bruno A.; Carter, Keith D.; Thurtell, Matthew J.
Abstract Wegener's granulomatosis often affects the orbit, typically presenting with painful proptosis. The authors describe a 14 year-old girl, with limited Wegener's granulomatosis, who initially presented with an isolated painless abduction deficit that spontaneously resolved over several weeks. She subsequently developed painful proptosis and diplopia, followed by facial and oral nodules. This case demonstrates that limited Wegener's granulomatosis can rarely present with an isolated painless abduction deficit.